2017
DOI: 10.1111/imj.13299
|View full text |Cite
|
Sign up to set email alerts
|

Association of type 2 diabetes with prolonged hospital stay and increased rate of readmission in patients with lower limb cellulitis

Abstract: A high proportion of patients with type 2 diabetes was admitted with LL cellulitis. They had significantly longer admissions and higher readmission rates. Age, HbA1c and ethnicity did not predict length of stay or recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…Diabetes has long been associated with increased risk of surgical site infection, sepsis and other healthcare-associated infections, and these dashboards have been designed to reduce the incidence Diabetes as an illness affects individuals through a progressive, multi-systemic nature. Not surprisingly, it has been associated with higher readmission rates for many different index hospitalizations [31,32]. Data from our dashboard agree with these prior studies, with an odds ratio for readmission for type 1 and type 2 diabetes in the USA being 1.66 and 1.27, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Diabetes has long been associated with increased risk of surgical site infection, sepsis and other healthcare-associated infections, and these dashboards have been designed to reduce the incidence Diabetes as an illness affects individuals through a progressive, multi-systemic nature. Not surprisingly, it has been associated with higher readmission rates for many different index hospitalizations [31,32]. Data from our dashboard agree with these prior studies, with an odds ratio for readmission for type 1 and type 2 diabetes in the USA being 1.66 and 1.27, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…A retrospective study from New York, USA, with 3692 patients with lower limb cellulitis found that older age, obesity, DM, low serum bicarbonate, high serum creatinine and elements of sepsis (tachycardia, hypotension, neutrophilia and leucocytosis) were all associated with a prolonged LOS . A retrospective case–control study from Auckland, New Zealand, with 3636 patients with lower limb cellulitis found that LOS was longer for patients with T2DM ( P < 0.001), but that age, HbA1c and ethnicity did not predict LOS or recurrence . A retrospective study from New South Wales, Australia, with 395 patients showed that factors independently associated with a prolonged LOS were age over 60, symptom duration of over 4 days, hypoalbuminaemia, bacteraemia and MRSA .…”
Section: Discussionmentioning
confidence: 99%
“…In Studien zum Erysipel wird der Diabetes mellitus oft nur als Grundkrankheit in der Anamnese mit aufgenommen oder als Komorbidität erfasst [2, 13,14]. Die Blutzuckerentgleisung [16,17] oder die Behandlung des Diabetes mellitus spielen selten eine wesentliche Rolle bei der Analyse [18]. Trotz oft hoher prozentualer Anteile der Patienten mit Diabetes mellitus Typ II unter den Patienten mit Erysipel wird dieser bei vielen Autoren nicht per se als Risikofaktor für das Erysipel eingestuft [19 -27], sondern nur angemerkt.…”
Section: Introductionunclassified